2022
DOI: 10.3390/nu15010178
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Administration of Cannabigerol Attenuates Inflammation and Fibrosis Associated with Methionine/Choline Deficient Diet-Induced NASH Model via Modulation of Cannabinoid Receptor

Abstract: Non-Alcoholic Steatohepatitis (NASH) is the progressive form of Non-Alcoholic Fatty Liver Disease (NAFLD). NASH is distinguished by severe hepatic fibrosis and inflammation. The plant-derived, non-psychotropic compound cannabigerol (CBG) has potential anti-inflammatory effects similar to other cannabinoids. However, the impact of CBG on NASH pathology is still unknown. This study demonstrated the therapeutic potential of CBG in reducing hepatic steatosis, fibrosis, and inflammation. Methods: 8-week-old C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Again, high concentrations of CBG, 10 µM CBG, and 30 µM CBG amplified the PA-F-induced secretion of TGF-β1. A previous study conducted by Aljobaily et al reported that a high concentration of CBG accelerated the inflammation state and the deterioration of NASH induced by a methionine/choline-deficient diet, which was reflected by an increased macrophage proliferation and infiltration [ 10 ]. These facts indicate that only a low concentration of CBG can suppress the palmitate and fructose-induced TGF-β1 activation and regulate the homeostasis of ECM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, high concentrations of CBG, 10 µM CBG, and 30 µM CBG amplified the PA-F-induced secretion of TGF-β1. A previous study conducted by Aljobaily et al reported that a high concentration of CBG accelerated the inflammation state and the deterioration of NASH induced by a methionine/choline-deficient diet, which was reflected by an increased macrophage proliferation and infiltration [ 10 ]. These facts indicate that only a low concentration of CBG can suppress the palmitate and fructose-induced TGF-β1 activation and regulate the homeostasis of ECM.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the non-psychotropic component of medical marijuana ( Cannabis sativa L.), namely, cannabigerol (CBG), appears to be a potential therapeutic agent for treating a variety of medical conditions. Studies indicate that CBG reduces the formation of reactive oxygen species in the intestinal epithelial cells during irritable bowel syndrome and also has potential anti-inflammatory effects that are similar to other cannabinoids [ 9 , 10 ]. Importantly, CBG acting on various receptors in the endocannabinoidome (eCBome) has an impact on the regulation of inflammation as well as processes related to lipid metabolism and overall hepatic metabolic functioning [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liver fibrosis represents a more progressive form of NAFLD that occurs if hepatic steatosis and inflammation persist for an extended period, leading to permanent damage to the liver [ 50 ]. If NAFLD progression remains untreated, permanent fibrotic damage can eventually promote hepatic cirrhosis and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…CBG is one of the main phytocannabinoids that has pharmacological significance as it does not exhibit psychotropic effects, but rather anti-inflammatory effects based on its binding to cannabinoid receptors even at concentrations as low as 0.1-1 μM (Navarro et al, 2018). Moreover, low doses of CBG alleviate inflammation and hepatic fibrosis; however, high doses of CBG may lead to the worsening of liver damage under oxidative conditions (Aljobaily et al, 2023). As far as its medical use is concerned, CBG has been proposed in therapies of prostate cancer (De Petrocellis et al, 2013) and glioblastoma (Lah et al, 2021), neuroprotection (García et al, 2018;Gugliandolo et al, 2018), antidiabetic action (Anokwuru et al, 2022), and in dermatology (Calapai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%